PENGARUH BUDAYA ORGANISASI DAN STRUKTUR ORGANISASI PADA SISTEM INFORMASI AKUNTANSI DAN DAMPAKNYA TERHADAP KUALITAS INFORMASI - Norman Alvi Tripambudi; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2014)
The purpose of this study is for examine the influence of organizational culture and organizational structure of the accounting information systems and their impact on the quality of information. This study is replication of previous research, Rapina (2013). Previous studies used 33 micro small and medium enterprises in Bandung. And in previous research used test equipment LISREL 8.7 with path analysis method of analysis. The population used in this study were listed in the Department of Cooperatives and SMEs in Central Java. Sampling technique in this study using a purposive sampling method, so this study used a sample of 40 micro small and medium enterprises in Semarang. This study used test equipment SPSS 21. Data analysis technique testing using multiple linear regression method. The results of this study indicated that the presence of organizational culture and organizational structure to supported the application of accounting information systems in used by the company. While the collaboration of good organizational culture, organizational structure, and accounting information systems can produced good quality information.